Sources of Volatility in Small Economies - Hnatkovska, Viktoria; Koehler-Geib, Fritzi (World Bank, Washington, DC, 2018)
Do sources of volatility differ by country characteristics such as the level of development, country size, quality of institutions, and presence of restrictions on fiscal policy? This paper sets out to answer this question in a quarterly panel of 48 developed and developing countries for 1960-2015. Using individual country and panel vector autoregressions, the paper shows that factors affecting gross domestic product volatility differ systematically by country size, development level, and whether a country has adopted fiscal rule(s). The role of country size is particularly pronounced in developing countries. The paper shows that small developing countries are more prone to domestic output shocks, while shocks to the world interest rate and real exchange rate are more important in large developing countries. Small countries are also more susceptible to terms of trade shocks. These results suggest that stabilization policies must be designed with these country characteristics in mind.